State regulation efficiency of food companies of Russia in sanction period - Baleevskikh, Alexander Sergeevich; Katlishin, Oleg Ilyasovich (Cuestiones Políticas, 2020)
The article is dedicated to the new political course of the Russian Federation, aimed at overcoming the economic blockade of the countries of Europe, as well as the United States. Effective management of food enterprises should take into account the new economic conditions for the functioning of the food economic subsector. In view of the crisis associated with the spread of coronavirus, falling oil prices, the ruble situation, the development of an economic course to adapt the Russian food industry becomes paramount. Therefore, the purpose of this article is a set of government measures to regulate the dairy food complex of the Russian Federation, both federally and regionally for the period 2008-2018. An analysis of the dynamics of milk industry indicators showed that the level of self-sufficiency for the period 2008-2018 was below the standard: 0.90. The study correlated the economics "import" and "self-sufficiency". Based on the data, it is concluded that the Russian Federation needs global innovation in the food industry mainly to the effective management of the agricultural dairy subsector.